(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: This qualitative study aimed to identify perceptions and acceptability among older Chinese adults in the United Kingdom (UK) of an adapted lifestyle-integrated exercise (aLiFE) programme, which seamlessly integrates balance and strength exercises into daily routines (e.g. doing one-leg stands while brushing teeth). This is part of a complex intervention, developing and evaluating a Chinese version of this falls prevention intervention (CLiFE). Method: Three sets of individual semi-structured interviews (partners: researcher, community leader, Tai Chi expert) and three focus groups (18 older Chinese adults (64–84) who live in the UK) were conducted to explore perceptions and acceptability of the adapted lifestyle-integrated exercise programme (aLiFE). Results of thematic analysis led to development of a draft adapted CLiFE programme. The draft is being co-designed further in workshops with older Chinese people and other partners. Results: Preliminary analysis identifies three key themes: current activity level and status, perception of cultural adaptation of movements, and perceptions of data collection methods. These findings provide evidence and valuable insights for the development of the CLiFE programme. Cultural modifications of aLiFE to develop CLiFE using co-design methods will be based on these findings. Conclusion: Findings indicated a high level of acceptance of aLiFE programme among older Chinese people in the UK, but the intervention needs cultural modification. Based on qualitative results and co-design workshops, a culturally adapted version, CLiFE, will be developed and tested within a future pre-post feasibility study with follow-up interviews. Support/Funding Source: This study is self-funded by the main researcher.